PELAFALAN KOSA KATA BAHASA INDONESIA BAGI PENUTUR ASING: (PEMBELAJAR THAILAND) MELALUI PENERAPAN DIRECT METHOD - Amelia, Gita; Febriyana, Mutia; Kemal, Isthifa (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
The language skills that will be a careful focus in this research are pronunciation skills. The object of research is Thai learners with Indonesian teachers as teachers and researchers. Data was analyzed using the observation method, namely jumping in and looking directly at the subject and object of interest. By using direct methods in teaching, the data obtained shows the ability of Thai learners to pronounce Indonesian vocabulary. This research is qualitative research looking at pronunciation ability as evidence of the success of teaching methods. At the first meeting of class VIII students, it was found that 5 out of 16 students knew simple Malaysian Malay, which was only spoken, not written. At the second meeting, 2 out of 16 students were able to spell names in Indonesian. In the third meeting, students were able to write their names in Indonesian and pronounce the alphabet. At the fourth meeting, errors were found in reading the text of 3 words on the blackboard, such as the word "saudara" being read as "suadara", "bersih" being read as "berseh" and several words with vowel combinations which made it difficult for the students to read the text. At the fifth meeting, students were able to read writing in one paragraph with several pronunciation errors, such as the letter C being pronounced SI. From this data it is known that the ability to pronounce Indonesian vocabulary by Thai learners has increased with each meeting.